Channel Modeling and Direction-of-Arrival Estimation in Mobile Multiple-Antenna Communication Systems - Ravari, Arastoo Rostami (2005)
Antennas that are able to adaptively direct the transmitted (and received) energy are of great interest in future wireless communication systems. The directivity implies reduced transmit power and interference, and also a potential for increased capacity. This thesis treats some modeling and estimation problems in mobile communication systems that employ multiple antennas, primarily at the base stations. With multiple antennas at the receive side, the spatial dimension is added, and processing is performed in both the temporal and spatial domains. The potential benefits are increased range, fading diversity and spatially selective transmission. Specifically, the problems dealt in this thesis are mainly related to the uplink transmission from mobile to the base station. Two main topics are studied, channel modeling and estimation of channel parameters. This thesis first describes the modeling of the reflected power distribution due to the scatterers close to the mobile stations, in terms of the received signal azimuth at the base station with multiple-antenna. As a more realistic channel modeling, a multipath fading deterministic channel model is proposed to generate properly correlated faded waveforms with appropriate power distribution through azimuth spread of received signal. The purpose of the proposed channel model is to model fading received signal waveforms with Laplacian distribution of power through received signal azimuth spread. This thesis is divided into two parts; in the first part multipath fading by local scattering are used to derive a channel model including the spatial dimension for non frequency-selective fading. This means that the mobile is not modeled as a point source but as a cluster of a large number of independent scatterers with small time delay spread to take into account angular spreading of the signal. Properly correlated fading waveforms are obtained by taking into account the angular spread of the scattered signals from a particular distribution of scatterers. By appropriate scaling of the array response vector (ARV) based on non-equal locations for various received signal components as a function of distance from the transmitter, the reflected power from a given scatterer is no longer constant but varies as a function of the distance from the transmitter. Our proposed channel model is able to produce fading signal waveform which agrees with the results of reflected angular power dispersions measured in the field, e.g. Laplacian distribution of power in azimuth. It is also shown that the channel response can be modeled as a complex Gaussian vector. Although the channel will be frequency selective in the case of multipath propagation with considerable time spread, this can be modeled as having more than one cluster of scatterers. By employing Walsh-Hadamard codewo VdLrs)l wideband multipath fading model is achieved. It is shown that the statistical properties of proposed model such as signal waveform's correlation, autocorrelation and crosscorrelation between generated paths, are in good agreement with the theory in space and time domain. The model can be applied to evaluate smart antenna systems and beamforming algorithms in the uplink by generating uncorrelated multipaths Rayleigh fading waveforms with certain spatio-temporal correlation and spatial coordinates relative to base stations to simulate received signals from mobiles and interferers. Bit-error-rate (BER) performance analysis of uniform linear array antenna (ULA) based on correlation - matrix is also presented as an application of our proposed model for multipleantenna evaluations. Our simulated results show 5% improvement than other published related works. One problem when modeling frequency selective fading is that each cluster has to be assigned spatial parameters. Since the joint spatial and temporal characteristics are unknown, non-parametric channel estimation approaches are required in this case in order to estimate the channel parameter, which is the subject of the second part. The second part of the thesis deals with channel parameter estimation of distributed scattering sources. Because of local scattering around the transmitter the signal waveforms appears spatially distributed at the receiver. The characterization of the spatial channel, in particular mean direction of arrival and spatial spread, is of prime interest for system optimization and performance prediction. Low-complexity spectral-based estimators are used for the estimation of direction and spatial spread of the distributed source by employing the proposed channel model for simulation. Estimated parameters from recent measurements ([PMFOO]) are compared with estimated parameters from model generated waveforms as well as theoretical distribution of received signal's angular spread. Good agreement between them is observed which shows the correctness of our proposed channel model for simulating spatio-temporally correlated received signal at an antenna array. The estimated parameter error improved by 5% over the other published related works.